1967
DOI: 10.1139/b67-234
|View full text |Cite
|
Sign up to set email alerts
|

Major and Minor Genes in Wheat for Resistance to Puccinia Striiformis and Their Responses to Temperature Changes

Abstract: The wheat varieties, 'P.I. 178383' and 'Chinese 166' (Triticum aestivum), were each found to carry an incompletely dominant major gene for resistance to a single pathogenic type of Puccinia striiformis. In addition, an undetermined number of minor genes segregated in such a way that in certain combinations they conferred moderate resistance and modified the action of the major genes. The rust readings were made on seedling plants grown in strictly controlled-environment chambers that simulated natural conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…Environmental influence on the reaction of wheat to P. striiformis f. sp. tritici has been found in several studies (Lewellen et al 1967;Lewellen & Sharp 1968;Milus & Line 1986) and this probably occurred in the present study. Sharp (1965) observed that cultivars showed characteristic responses to increasing temperature profiles.…”
Section: Parents or Dh Linessupporting
confidence: 86%
See 2 more Smart Citations
“…Environmental influence on the reaction of wheat to P. striiformis f. sp. tritici has been found in several studies (Lewellen et al 1967;Lewellen & Sharp 1968;Milus & Line 1986) and this probably occurred in the present study. Sharp (1965) observed that cultivars showed characteristic responses to increasing temperature profiles.…”
Section: Parents or Dh Linessupporting
confidence: 86%
“…The heterozygote major gene would probably condition an MR reaction by itself, but with the modifying influence of the resistance factor it appeared to condition the IT near to an R type in the F 1 of 'Tiritea' x 'Otane'. This kind of additive and major/minor gene resistance has been reported by many workers (Lewellen et al 1967;Milus & Line 1986;Ma & Singh 1997) for resistance to stripe rust in wheat.…”
Section: Parents or Dh Linessupporting
confidence: 65%
See 1 more Smart Citation
“…Sharp and associates [42][43][44][45] were the first to study inheritance of stripe rust resistance that are temperature sensitive. They identified three minor genes in wheat genotype 'PI 178383' and found them under influence of temperature.…”
Section: Genetics Of Htap Resistancementioning
confidence: 99%
“…To assess the effectiveness of different test inducer treatments in suppressing the disease, infection type and disease severity on the two wheat cultivars were recorded fifteen days after treatments. Infection types were assessed using a scale described by Lewellen et al (1967) as follows: 0 = no visible infection; R = resistant, necrotic area with or without small pustules; MR = moderately resistant, small pustule surrounded by necrotic area; M = intermediate resistance, pustules of variable size, some necrosis or chlorosis; MS = moderately susceptible, medium sized pustules, no necrosis but some chlorosis and S=susceptible, large pustules, no necrosis or chlorosis. At the same time, disease severity was estimated by using the modified Cobb scale (Peterson et al 1948).…”
Section: Methodsmentioning
confidence: 99%